2019
DOI: 10.1186/s13104-019-4198-z
|View full text |Cite
|
Sign up to set email alerts
|

Community-led data collection using Open Data Kit for surveillance of animal African trypanosomiasis in Shimba hills, Kenya

Abstract: ObjectiveIn Sub-Saharan Africa, there is an increase in trypanosome non-susceptibility to multiple trypanocides, but limited information on judicious trypanocide use is accessible to smallholder farmers and agricultural stakeholders in disease endemic regions, resulting in widespread multi-drug resistance. Huge economic expenses and the laborious nature of extensive field studies have hindered collection of the requisite large-scale prospective datasets required to inform disease management. We examined the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…About 89% of the households were headed by men, who were 54 years old on average. These results are consistent with recent findings in the study area by Wamwenje et al (2019). Markakis (2004) also observed that men are the decision makers in livestock-keeping households, as they have more access and rights to economic resources compared to women.…”
Section: Descriptive Statisticssupporting
confidence: 92%
“…About 89% of the households were headed by men, who were 54 years old on average. These results are consistent with recent findings in the study area by Wamwenje et al (2019). Markakis (2004) also observed that men are the decision makers in livestock-keeping households, as they have more access and rights to economic resources compared to women.…”
Section: Descriptive Statisticssupporting
confidence: 92%
“…The increasing use of electronic data collection and electronic data interchange by surveillance systems promotes timeliness and increases the usefulness of reporting ( 20 ). Mobile-based surveillance systems are known to capture higher numbers of AH events compared to traditional surveillance systems ( 68 , 81 ). This is evident from the progressive improvement in reporting rates following the progressive roll-out of KABS, as seen in Figure 3 .…”
Section: Discussion: Utility Of Animal Health Surveillance In Kenya F...mentioning
confidence: 99%
“…Practitioners found prospective data collection forms relatively easy to use and on-farm recording was believed to maximize accuracy. Subsequent transfer to an electronic format was somewhat more time consuming; utilization of a mobile off-line data collection tool could streamline this process [ 33 ]. The data collection forms represented a compromise between participants’ desire for detailed information against perceived time constraints and client acceptance of data recording.…”
Section: Discussionmentioning
confidence: 99%